Dynamique reproductive de la camarine noire (Empetrum nigrum L.) le long d'une chronoséquence de feu à la limite des arbres. Issue 3 (1st October 2016) - Villeneuve-Simard, Marie-Pascale; Boudreau, Stéphane
ABSTRACT: The relative importance of sexual reproduction and clonal growth for the long-term maintenance of crowberry populations is poorly understood. Our objective was to characterize reproductive output, recruitment and clonal growth in different populations along a fire chronosequence at the treeline. Our research hypothesis was that sexual reproduction would be more important in younger sites, but that clonal growth would be prevalent in older sites. We quantified cover and reproductive output and reconstructed the establishment chronology of the crowberry populations. The positive relationship between crowberry cover and site age is mainly attributable to the presence of a tree cover at older sites. Fruit production, lower in forested sites, and seed viability were not related to site age. Recruitment of individuals appeared to be relatively similar between sites, while the number of clonal individuals increased with the time elapsed since the last fire. Our results partially support our research hypothesis. While clonal growth is more important for population maintenance at older sites, the species keeps investing in sexual reproduction, even when dominant.